Samurai heraldry - Turnbull, Stephen (Elite series ;, 2014)
The dazzling spectacle presented by the armies of medieval Japan owed much to the highly developed family and personal heraldry of samurai society. From simple personal banners, this evolved over centuries of warfare into a complex system of flags worn or carried into battle, together with the striking 'great standards' of leading warlords. While not regulated in the Western sense, Japanese heraldry developed as a series of widely followed practices, while remaining flexible enough to embrace constant innovation. Scores of examples, in monochrome and full colour, illustrate this fascinating explanation of the subject by a respected expert on all aspects of samurai culture.